2011
DOI: 10.1007/s11103-011-9826-5
|View full text |Cite
|
Sign up to set email alerts
|

Activity of transcription factor JACKDAW is essential for SHR/SCR-dependent activation of SCARECROW and MAGPIE and is modulated by reciprocal interactions with MAGPIE, SCARECROW and SHORT ROOT

Abstract: Two GRAS family transcription factors, SHORT-ROOT (SHR) and SCARECROW (SCR), are required for ground tissue and quiescent center formation in Arabidopsis roots. The action of SHR and SCR is regulated by two INDETERMINATE DOMAIN (IDD) family proteins, JACKDAW (JKD) and MAGPIE (MGP). Although the reciprocal interaction of these transcription factors is considered to be involved in the modulation of SHR and SCR action by JKD and MGP, the underlying mechanism remains unclear. In this study, we use a transient assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 26 publications
0
63
0
1
Order By: Relevance
“…JACKDAW and MAGPIE act downstream of SHORTROOT and SCARECROW in establishing radial pattern and cell identities in the root apex (Welch et al, 2007;Hassan et al, 2010;Ogasawara et al, 2011). IDD4 and several other IDD genes are direct targets of regulation by REVOLUTA and KANADI, implicated in establishing the adaxial/abaxial pattern and cell fates in leaves and other lateral organs (Reinhart et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…JACKDAW and MAGPIE act downstream of SHORTROOT and SCARECROW in establishing radial pattern and cell identities in the root apex (Welch et al, 2007;Hassan et al, 2010;Ogasawara et al, 2011). IDD4 and several other IDD genes are direct targets of regulation by REVOLUTA and KANADI, implicated in establishing the adaxial/abaxial pattern and cell fates in leaves and other lateral organs (Reinhart et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin immunoprecipitation provided evidence for the association in vivo of other GRAS proteins with promoters of their putative target genes, such as DELLA (Zentella et al, 2007) and SHORTROOT (SHR;Cui et al, 2007). Although a role in the transcriptional regulation of their putative targets has been reported for other GRAS factors, in most cases they seem to act as coactivators (Morohashi et al, 2003;Ogasawara et al, 2011). As for NSP1 and NSP2, SHR and SCARECROW (SCR) GRAS TFs are unable to significantly activate transcription without associating with other TFs.…”
Section: Discussionmentioning
confidence: 99%
“…To quantify the effect of BIRD proteins in retaining nuclear SHR, we measured nuclear and cytoplasmic SHR-YFP fluorescence intensity in the vasculature with ectopic SCR or BIRD proteins expression and found that in the roots, the presence of BIRD proteins enhanced SHR nuclear portion to similar levels as SCR (Supplemental Figure 6F). As JKD is required to activate SCR expression (Ogasawara et al, 2011), we tested whether SHR nuclear localization mediated by JKD and BIB operated in part through induction of SCR. We first analyzed SCR expression in lines misexpressing JKD and BIB in the vascular domain and found that SCR was ectopically induced in the vascular tissue ( Figures 3F to 3I').…”
Section: Bib and Jkd Cooperate With Scr To Retain Shr In The Nucleusmentioning
confidence: 99%